The Minister Historian, The Granadian Ibnul Khateeb, The Sheikh of Granada scientists (Journal of the College of Education for Women, 2019)
1- The Granadian, Lisan Ad-Din Ibn ul Khateeb, was a brilliant thinker and a great writer who filled Andalus and Morocco with literature and poetry and his genius emerged in different knowledge fields.2- He was one of Andalus famous people, as he was a first class physician and philosopher, a great historian, a farsighted politician and had a strong cognition.3- Ibnul Khateeb proved that his age, that he lived in, was a sophisticated in which arts, literatures and sciences thrived.4- Ibnul Khateeb dedicated his life for the service of Granada Kingdom and that was clear in his writings, both prose and poetry.5- Ibnul Khateeb witnessed a group of great Andalus scientists and writers, firstly the thinker Ibn Khaldun who singled out his friendship after meeting him in Andalus and they were exchanging letters.6- All Ibnul Khateeb's valuable authors in the historic, geographical, literary, Islamic and scientific fields were considered as a vessel never be empty for those who search and study in civilization history for Arabs and Muslims of Andalus